Above-ground space sequestration determines competitive success in juvenile beech and spruce trees - Kozovits, A.R; Matyssek, R; Winkler, J.B; Gottlein, A; Blaschke, H; Grams, T.E.E (The New phytologist, 2005)
$\bullet$ A 2-yr phytotron study was conducted to investigate the intra- and inter-specific competitive behaviour of juvenile beech (Fagus sylvatica) and spruce (Picea abies). Competitiveness was analysed by quantifying the resource budgets that occur along structures and within occupied space of relevance for competitive interaction. $\bullet$ Ambient and elevated CO2 and ozone (O3) regimes were applied throughout two growing seasons as stressors for provoking changes in resource budgets, growth and allocation to facilitate the competition analysis. The hypothesis tested was that the ability to sequester space at low structural cost will determine the competitive success. $\bullet$ Spruce was a stronger competitor than beech, as displayed by its higher above-ground biomass increments in mixed culture compared with monoculture. A crucial factor in the competitive success of spruce was its ability to enlarge crown volume at low structural costs, supporting the hypothesis. $\bullet$ Interspecific competition with spruce resulted in a size-independent readjustment of above-ground allocation in beech (reduced leaf : shoot biomass ratio). The efficient use of resources for above-ground space sequestration proved to be a parameter that quantitatively reflects competitiveness.